Addressing Food Insecurity Through Community Kitchens During the COVID-19 Pandemic: A Case Study from the Eastern Cape, South Africa - Joana Carlos Bezerra; Thandiswa Nqowana; Rene Oosthuizen; Monica Canca; Nosipho Nkwinti; Sukhmani Kaur Mantel; Mark New; James Ford; Carol Claudia Zavaleta-Cortijo; Eranga K. Galappaththi; Chrishma D. Perera; Sithuni M. Jayasekara; et al. (Urban Science)
One of the most critical impacts of the COVID-19 pandemic was on food security. Food insecurity increased in many communities, with some showing signs of resilience through autonomously creating community kitchens that enhanced food security and built support networks. These initiatives filled gaps left by government programmes and provided a critical lifeline for vulnerable communities during the pandemic, fostering community solidarity. This paper aims to investigate the experiences and perceptions of community kitchen managers in addressing food insecurity during the COVID-19 pandemic by using a town in South Africa in 2020–2022 as a case study. Using arts-based participatory approaches, researchers interviewed 11 community kitchen managers representing 10 community kitchens in four sessions between June and November 2021. The results showed that a lack of jobs and food insecurity were identified as the main threats, whereas COVID-19 was not even identified as a threat by all of the community kitchen managers. Lacking support from the local government, these initiatives depended on individuals and community-based organisations for backing. However, this support decreased in 2021 and 2022, raising concerns about the sustainability of these efforts.